AF-equivalence relations - Molberg, Mats (MATHEMATICA SCANDINAVICA, 2006)
Let R=_R_n be the inductive limit of an ascending sequence of étale finite equivalence relations R_n on the zero-dimensional space X. We prove that R is an AF-equivalence relation.